Research: A Pathway Towards a Good Curriculum Vitae - Muhammad T. Shakoor; Samia Ayub; Zunaira Ayubs (University Library System, University of Pittsburgh, 2013)
Nowadays there is a lashing trend of doing fellowships. Residency and fellowship positions have become very competitive. From my experience, I found that the majority of candidates who aspire to apply for residency or fellowship positions don't have any significant research backgrounds. Being a medical student myself, I should not blame any other student for this deficiency, as most of the medical schools don't provide basic atmosphere, guidance and infrastructure for undergraduate research activities. By the time students graduate and apply for a residency spot or fellowship position after residency, they have no research credentials with them other than their degree requirements and a few certificates for extracurricular activities. One should realize that these accomplishments merely provide a skeleton for your Curriculum vitae (CV) in order to add depth to your CV you have to be able to include research experiences (that you have acquired during your undergraduate degree), as well as good recommendation letters and advanced clinical experience.1 Research work in your CV will help set you apart. When you go for a job interview, having a strong research background and independent work gives you something to talk about that the interviewer will be interested in. As a student, any efforts in the field of research are highly appreciated. Above all, research training will make you a better-equipped physician with a sharper mind and stronger critical thinking skills.